2018
DOI: 10.1002/jcad.12220
|View full text |Cite
|
Sign up to set email alerts
|

Counselors’ Mandated Responsibility to Report Child Maltreatment: A Review of U.S. Laws

Abstract: Although counselors in 44 states are mandatory reporters of child maltreatment, they may lack an understanding of their legally designated role. This article presents the results of a systematic review of child maltreatment reporting laws in all 50 states and the District of Columbia. The authors apply relevant legislation to real‐life contexts for counselors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…For example, because many of these state policies define affirmative medical care for TGD youth as child abuse, mental health professionals may find themselves in an ethical conflict when providing services to TGD children and their families; and specifically for parental figures of TGD children under the age 18. Although it is unclear from the antitransgender laws being passed exactly how should mental health providers handle the conflict between supporting TGD children and their families in accordance with current standards of care versus legal requirements, it is crucial for mental health providers to become intimately aware of what constitutes child abuse in their state (see review in Kenny et al, 2018), the Standards of Care for the Health of Transsexual, Transgender, and Gender-Nonconforming People (Coleman et al, 2012), and mental health organizations’ guidelines for working with transgender people (e.g., American Psychological Association, 2015). To take these recommendations a step further, we pose that it is not only the ethical responsibility of mental health providers to oppose these bills, but their duty to engage in acts of civil disobedience to protect TGD people and their families (see Flynn et al, 2021 for a review).…”
Section: Discussionmentioning
confidence: 99%
“…For example, because many of these state policies define affirmative medical care for TGD youth as child abuse, mental health professionals may find themselves in an ethical conflict when providing services to TGD children and their families; and specifically for parental figures of TGD children under the age 18. Although it is unclear from the antitransgender laws being passed exactly how should mental health providers handle the conflict between supporting TGD children and their families in accordance with current standards of care versus legal requirements, it is crucial for mental health providers to become intimately aware of what constitutes child abuse in their state (see review in Kenny et al, 2018), the Standards of Care for the Health of Transsexual, Transgender, and Gender-Nonconforming People (Coleman et al, 2012), and mental health organizations’ guidelines for working with transgender people (e.g., American Psychological Association, 2015). To take these recommendations a step further, we pose that it is not only the ethical responsibility of mental health providers to oppose these bills, but their duty to engage in acts of civil disobedience to protect TGD people and their families (see Flynn et al, 2021 for a review).…”
Section: Discussionmentioning
confidence: 99%
“…MR is a mechanism instituted by law that requires certain professionals to report suspected child maltreatment to child protection authorities and has been a model used for decades to protect those who may be experiencing abuse or neglect, to connect individuals and families to needed services, and to prevent future abuse and neglect (Kenny et al, 2018; Mathews & Bross, 2008, 2015; Raz, 2017). MR policies have rapidly expanded, though, over the last several years to now include those most affected by abuse and neglect.…”
Section: History Of and Variation In Mr Policy In The United Statesmentioning
confidence: 99%
“…73 Research has found that education on reporting laws is key to competence in reporting. 74 The Form 22 set out in the regulations to the Children's Act must be completed for each child by a mandatory reporter and contains guidance as to what is reasonable and suspicious. However, Jamieson et al's study revealed that only 5% of the reports were recorded on the prescribed form.…”
Section: Lack Of Understanding Reporting Legislation and Hard Evidencementioning
confidence: 99%